Kajian Etnoarkeologi Terhadap Masyarakat Petani Padi Bukit Suku Temiar Di Rps Pasik, Hulu Kelantan - Hashim, Nur Athmar (2013)
Ethnoarchaeological study on Temiar hill rice farmers which involved field work has been conducted in RPS Pasik, Gua Musang, Hulu Kelantan on October 2010 until March 2011, followed by laboratory analyses and report writing. This research was carried out in order to understand the pattern of technology and adaptation of early Neolithic agriculturalist. A systematic methodology was applied using archaeological and ethnographical approach. Archaeological approaches, through survey and mapping were conducted to map the distribution of sites studied and other related data. In addition, experiment on useware was conducted to test the function of ‘Tembeling Knife’. Ethnographical approaches were applied through participation observation, interviewed (open and indepth), questionaires, and recording through photos, drawing and field note. Qualitative and quantitative data collected were analysed and interpreted. This study aims to answer issues pertaining early Neolithic agriculturalist particularly on their agricultural patterns, technology and adaptation, belief, social structure, and also on the function of the ‘Tembeling Knife’.